ACCELERATED TEST TO DETERMINE THE CORROSION BEHAVIOR OF STEELS IN BOILERS BURNING SUGARCANE BIOMASS - Abel Rivas Gutierrez; Carlos Lariot Sánchez; Beatriz Concepción Rosabal; Lizet Rodríguez Machín (Revista Centro Azúcar)
Introduction: In order to increase the percentage of sugarcane agricultural residues used in a mixture with bagasse to generate electricity in biomass boilers, it is necessary to study the corrosion behavior caused in superheater tubes due to its high content of alkalis and chlorides compared to bagasse. Objective: To develop a tentative accelerated test, at laboratory scale, to predict the corrosion behavior, in high temperature zones, of type steels used in the superheater of high parameter steam generators. Materials and Methods: Metallography of steels, determination of composition and creation of synthetic ash to be used, corrosion rate calculation and analysis at the steel/oxides/deposits interface. Results and Discussion: In both steels studied, an increase in the corrosion rate was observed for the synthetic ash composition of the similar composition to that of higher concentration of sugarcane agriculture residues. Similarly, a greater thickness of oxide layers was observed when the steels were treated with synthetic ashes of composition similar to that of higher percentage of residues mixed with bagasse. Conclusions: This study carried out allowed to determine, comparatively, the behavior in the first stages of corrosion at 540 °C of two steels used in the construction of high-parameter superheaters boilers attacked by ashes simulating those formed in the combustion of different concentrations of sugarcane agricultural residues mixed with bagasse.